If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8d + -1.3(6 + -9d) = 42 8d + (6 * -1.3 + -9d * -1.3) = 42 8d + (-7.8 + 11.7d) = 42 Reorder the terms: -7.8 + 8d + 11.7d = 42 Combine like terms: 8d + 11.7d = 19.7d -7.8 + 19.7d = 42 Solving -7.8 + 19.7d = 42 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '7.8' to each side of the equation. -7.8 + 7.8 + 19.7d = 42 + 7.8 Combine like terms: -7.8 + 7.8 = 0.0 0.0 + 19.7d = 42 + 7.8 19.7d = 42 + 7.8 Combine like terms: 42 + 7.8 = 49.8 19.7d = 49.8 Divide each side by '19.7'. d = 2.527918782 Simplifying d = 2.527918782
| 2c+6=10 | | 132=-4(5n-3) | | 4(7-5x)=12(8+4x) | | 44+i/i | | X=0.74 | | 7/6x=420 | | -2x-1=-9-x | | 7(-5+6x)=-35 | | 2x+7+3x+5=27 | | 3/5x=-3 | | -5a+5-3=4 | | 8y=-8x-8 | | 8(x-3)-4x=4 | | -1p-5p=18 | | 7x-3x=-x+50 | | 3u-7+3(2u+5)=-3(u+2) | | (-1/2)^2 | | -8p+6+9p=-17+p | | -6(1x+1)=60 | | m-3= | | 3/8-1/4t=1/2t-34 | | 4(d+6)=32 | | 3(y-10)+1=2(y-8) | | (13+i)/i | | ((x^2+29)/(x^2-4x-5))-((x+4)/(x-5)) | | 4(w+5.2)=26 | | -3(v-4)=8v+34 | | 3(2x+5)=5x+15+x | | 6w+4w=50 | | 4(5+2x)=28 | | 7-1/16=-2 | | ((13+i)/i) |